2021
DOI: 10.1155/2021/9054812
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy C-Means Algorithm-Based Adoption of Obturator Nerve Block under Adaptive Ultrasound Imaging for Bladder Tumor

Abstract: This work aimed to study the adoption of obturator nerve block (ONB) based on adaptive medical ultrasound imaging under C-means algorithm in transurethral resection of bladder tumor (TURBT). 120 patients with bladder tumors were diagnosed by C-means algorithm-based ultrasound imaging and were enrolled into group A (epidural anesthesia + resection), group B (general anesthesia), and group C (epidural anesthesia + ONB), each with 40 cases. The accuracy of the detection method, noise level, and complications befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This study also found that the observation group had better urinary function than the control group, indicating that this treatment method can improve patients' urinary function. The procedure is simple, precise, provides a clear surgical view for the attending physician, and the laser does not generate electric currents, which can avoid urethral stricture and promote the recovery of urinary function [14,15]. Furthermore, this study found that the complication rate in the observation group was lower than that in the control group.…”
Section: Discussionmentioning
confidence: 58%
“…This study also found that the observation group had better urinary function than the control group, indicating that this treatment method can improve patients' urinary function. The procedure is simple, precise, provides a clear surgical view for the attending physician, and the laser does not generate electric currents, which can avoid urethral stricture and promote the recovery of urinary function [14,15]. Furthermore, this study found that the complication rate in the observation group was lower than that in the control group.…”
Section: Discussionmentioning
confidence: 58%